Genetic structure and contrasting selection pattern at two major histocompatibility complex genes in wild house mouse populations - Cížková, D; Gouy de Bellocq, J; Baird, S J E; Piálek, J; Bryja, J (Heredity, 2011)
The mammalian major histocompatibility complex (MHC) is a tightly linked cluster of immune genes, and is often thought of as inherited as a unit. This has led to the hope that studying a single MHC gene will reveal patterns of evolution representative of the MHC as a whole. In this study we analyse a 1000-km transect of MHC variation traversing the European house mouse hybrid zone to compare signals of selection and patterns of diversification at two closely linked MHC class II genes, H-2Aa and H-2Eb. We show that although they are 0.01 cM apart (that is, recombination is expected only once in 10 000 meioses), disparate evolutionary patterns were detected. H-2Aa shows higher allelic polymorphism, faster allelic turnover due to higher mutation rates, stronger positive selection at antigen-binding sites and higher population structuring than H-2Eb. H-2Eb alleles are maintained in the gene pool for longer, including over separation of the subspecies, some H-2Eb alleles are positively and others negatively selected and some of the alleles are not expressed. We conclude that studies on MHC genes in wild-living vertebrates can give substantially different results depending on the MHC gene examined and that the level of polymorphism in a related species is a poor criterion for gene choice.
Keywords: alely; molekulární evoluce; sekvenční seřazení; sekvence nukleotidů; DNA primery; Gene Components; populační genetika; Hybridization, Genetic; Phylogeny; Molecular Sequence Data; Evolution, Molecular; Genetics, Population; genetické komponenty; molekulární sekvence - údaje; Cluster Analysis; Alleles; zvířata; myši; hybridizace genetická; Mice; genetická variace; Amino Acid Sequence; Genetic Variation; Base Sequence; Major Histocompatibility Complex; modely genetické; fylogeneze; Sequence Alignment; shluková analýza; DNA Primers; hlavní histokompatibilní komplex; Models, Genetic; Animals; selekce (genetika); Selection, Genetic; sekvence aminokyselin